Photochemical activity in developing pea (Pisum sativum L.) cotyledons depends on the light transmittance of covering tissues and the spectral composition of light - G. N. Smolikova; N. V. Stepanova; A. M. Kamionskaya; S. S. Medvedev (Вавиловский журнал генетики и селекции, 2023)
Many crops require not only leaf photosynthesis for their seed development but also the photochemical reactions that occur in the seeds. The purpose of this work was a comparative analysis of light transmittance and photochemical activity in the leaves of Pisum sativum L. and its pericarp, seed coat, and cotyledons at the early, middle, and late maturation stages. The spectral composition of light was measured using a spectroradiometer in the range of 390–760 nm. We assessed the light transmittance of plant tissues by placing the plant tissue between the light source and the spectroradiometer’s sensor. PAM fluorometry was used to quantify the photochemical activity in plant tissues: this technique is handy for evaluating the efficiency of converting light energy into chemical energy through the analysis of the kinetics of chlorophyll fluorescence excitation and quenching. On average, a photochemically active green leaf of pea transmitted 15 % of solar radiation in the 390–760 nm, blue light was delayed entirely, and the transmitted red light never exceeded 5 %. Photochemically active radiation passing through the pericarp and coat and reaching the cotyledons at the early and middle seed maturation stages manifested a high proportion of green and far-red light; there was no blue light, and the percentage of red light was about 2 %. However, the cotyledons were photochemically active regardless of low irradiance and spectral ranges untypical of leaf photosynthesis. At the early and middle maturation stages, the maximum quantum yield of photosystem II (Fv/Fm) averaged 0.5 at the periphery of cotyledons and 0.3 at their center. Since the intensity of embryonic photochemical reactions significantly affects the efficiency of reserve nutrient accumulation, this parameter is a promising marker in pea breeding for seeds with improved nutritional qualities.